2016
DOI: 10.1155/2016/3816184
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcus Colonization among Pregnant Women Attending Antenatal Care at Tertiary Hospital in Rural Southwestern Uganda

Abstract: Objectives. This study sought to determine the prevalence and factors associated with group B streptococcal anogenital colonization among pregnant women attending antenatal care at Mbarara Regional Referral Hospital, a tertiary hospital. Methods. Cross-sectional study where 309 pregnant women ≥ thirty-five weeks of gestation attending antenatal clinic were consecutively recruited between January and March 2015. Anovaginal swabs were collected and tested qualitatively using rapid visual immunoassay GBS test kit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 12 publications
4
10
6
Order By: Relevance
“…Increasing epidemiological studies have demonstrated the relationship between obesity and GBS colonisation in pregnant women, but current evidence is inconsistent. 7,8,26 When BMI was classified as ≤28 kg/m 2 and >28 kg/m 2 , obesity was associated with significantly increased rate of GBS colonisation in this study (OR = 3.79), which is consistent with the findings from Uganda and Washington State using the same cut-off for BMI classification. 7,8 When BMI was categorised into three groups (<18.5, 18.5-24.9, or ≥25 kg/m 2 ), significant differences were also found in this study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Increasing epidemiological studies have demonstrated the relationship between obesity and GBS colonisation in pregnant women, but current evidence is inconsistent. 7,8,26 When BMI was classified as ≤28 kg/m 2 and >28 kg/m 2 , obesity was associated with significantly increased rate of GBS colonisation in this study (OR = 3.79), which is consistent with the findings from Uganda and Washington State using the same cut-off for BMI classification. 7,8 When BMI was categorised into three groups (<18.5, 18.5-24.9, or ≥25 kg/m 2 ), significant differences were also found in this study.…”
Section: Discussionsupporting
confidence: 89%
“…7,8,26 When BMI was classified as ≤28 kg/m 2 and >28 kg/m 2 , obesity was associated with significantly increased rate of GBS colonisation in this study (OR = 3.79), which is consistent with the findings from Uganda and Washington State using the same cut-off for BMI classification. 7,8 When BMI was categorised into three groups (<18.5, 18.5-24.9, or ≥25 kg/m 2 ), significant differences were also found in this study. However, when using another binary variable of BMI (≤23 kg/m 2 vs >23 kg/m 2 ), no significant association was observed in our study but a significant negative association was observed in the Karachi study using the same cut-off.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, much lower prevalence rate of 1.33% was reported in Uyo (19) and 6.6% was reported in Jos, Nigeria (20). On the contrary, higher prevalence rates of 14%, 28.8% and 21.61% have been reported in earlier studies in Zaria, Nigeria (21), Uganda (22) and South Africa (23), respectively. A study in the DRC reported overall colonization rate of 20% amongst pregnant women (12).…”
Section: Discussionmentioning
confidence: 55%